Introducing anthropology of religion - Eller, Jack David, 1959- author.
1 online resource.
Keywords: "This clear and engaging guide introduces students to key areas of the field and shows how to apply an anthropological approach to the study of religion in the contemporary world. Written by an experienced teacher, it covers major traditional topics including definitions, theories and beliefs as well as symbols, myth and ritual. The book also explores important but often overlooked issues such as morality, violence, fundamentalism, secularization, and new religious movements. The chapters all contain lively case studies of religions practiced around the world. The third edition of Introducing Anthropology of Religion is fully updated and contains additional content on material religion, visual religion, and affect theory and a new chapter takes a closer look at medical and health topics. The author encourages the reader to engage throughout with the unifying themes of race, gender and power, and how these themes are intertwined with anthropology of religion. Images, a glossary and questions for discussion are included and additional resources are provided via a companion website"--